A Human Reliability Assessment of Marine Engineering Students through Engine Room Simulator Technology. (October 2021) - Kandemir, , Cagatay; Celik, Metin
Background: It is widely accepted that the simulators are important technological instruments which can be utilized as an effective assessment tool in various domains Developing technologies allow the functionality levels of simulators to increase behavioural realism. For this reason, students in higher educations are involved in various useful practices using simulators. Purpose: In this respect, simulators can also provide great opportunities to conduct analysis through human error on which this study conceptualized. Model: In this context, this study proposes a human error evaluation approach throughsimulator technology whilst taking advantage of the SOHRA (Shipboard Operation Human Reliability Analysis) method. As a case study, the proposed approach was applied to a simulator environment with the involvement ofmarine engineering students. Throughout this case, the students were challenged with various error producing conditions (EPCs) while their performances were observed. Results: The attendees were achieved good practice when confronted with EPC23 (unreliable instruments), EPC17 (inadequate checking), and EPC5 (spatial & functional incompatibility). However, the points open for improvement are found on EPC2 (time shortage), EPC24 (absolute judgments required), EPC18 (objectives conflict) and EPC9 (technical unlearning). Conclusion: This framework can be utilized in simulator-based training activities to increase operational awareness of marine engineering students. The recent developments insimulator technology can boost the effectiveness of the proposed framework.